L'Antiquité dans l'art médiéval : Regards historiographiques et méthodologiques - Terrier Aliferis, Laurence (My University, 2019)
The imitation of Antique art during the medieval period is a theme that benefits from an important historiographical tradition. Through it, the research trends that have dominated this field for these past twenty-five years can be brought to light. It is telling that after the founding work of the 1930s to the 1960s, which focalised on the survival-revival duality, the research no longer considers this theme from a global point of view. Instead, punctual studies are conducted on specific aspects. A state of the research from the beginning of the 1990s onwards is proposed here, pointing out the various domains discussed. Questions of model localisation and the intentions behind imitating the past motivate most studies undertaken in the past few decades. The most important finding of the recent research, however, is the realisation that the medieval objects were appreciated for purely esthetical reasons during the re-use/imitation process.
Keywords: Antiquity; spolia; esthetic; historiography; renascences